2016
DOI: 10.1093/rheumatology/kew402
|View full text |Cite
|
Sign up to set email alerts
|

Predicting cardiopulmonary involvement in patients with systemic sclerosis: complementary value of nailfold videocapillaroscopy patterns and disease-specific autoantibodies

Abstract: In Dutch SSc patients, all SSc-specific auto-antibodies were found, with ACA and anti-Scl-70 being the most prevalent. Strikingly, the association between NVC-pattern and heart/lung involvement was independent of specific anti-ENA antibodies, which might indicate microangiopathy is an important cause of organ involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
49
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 27 publications
7
49
1
4
Order By: Relevance
“…In addition, the single NVC pattern and its score may be of great value to predict novel future SSc organ involvement, as recently demonstrated [9,19,38]. Previous studies have demonstrated the positive effects of therapeutic approaches on microvascular damage in SSc [1214].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the single NVC pattern and its score may be of great value to predict novel future SSc organ involvement, as recently demonstrated [9,19,38]. Previous studies have demonstrated the positive effects of therapeutic approaches on microvascular damage in SSc [1214].…”
Section: Discussionmentioning
confidence: 99%
“…Capillaroscopic abnormalities were associated with a mean 15% reduction in forced vital capacity and DLCO compared to participants with normal capillaroscopy findings. Multiple other studies have also found an association between abnormal capillaroscopy and the presence or severity of ILD [27,34,46].…”
Section: Interstitial Lung Diseasementioning
confidence: 89%
“…Because of its relatively lower prevalence than other organ specific manifestations, it is more difficult to explore the role of NFC in predicting its presence or severity but some studies have already shown some intriguing results. In a recent Dutch cohort of over 200 patients, NFC changes were independently predictive of cardio-respiratory complications and, notably, all patients with pulmonary hypertension had abnormal NFC [46]. The "late" pattern and reduced capillary density have both been associated with the presence and severity of pulmonary hypertension in SSc [47,48].…”
Section: Pulmonary Hypertensionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is well known that the patterns of NVC scleroderma spectrum abnormalities are closely correlated to organ involvement in patients with SSc [22]. Interstitial lung disease and pulmonary artery hypertension [23] and skin ulcers [24] are common in cases with NVC scleroderma spectrum abnormalities. In particular, the loss of capillaries with extensive avascular areas is an important finding, and there are many reports that a late NVC pattern suggests the presence of organ involvement.…”
Section: Correlation Between Patterns Of Nvc Scleroderma Spectrum Abnmentioning
confidence: 99%